Glycoengineering of the hepatitis C virus E2 glycoprotein improves biochemical properties and enhances immunogenicity - Liudmila Kulakova; Kiki H. Li; Austin W. T. Chiang; Michael P. Schwoerer; Saori Suzuki; Sanne Schoffelen; Khadija H. Elkholy; Kinlin L. Chao; Salman Shahid; Bhoj Kumar; Nathan B. Murray; Stephanie Archer-Hartmann; et al. (npj Vaccines)
Abstract An effective vaccine against hepatitis C virus (HCV) must elicit the production of broadly neutralizing antibodies (bnAbs) reproducibly against the E1E2 glycoprotein complex. Little is known about how glycan content affects this process. Ideally, glycans would maximize epitope exposure without compromising antigen stability or exposing new epitopes. However, typical recombinant vaccines contain considerable heterogeneity in glycan content, which can affect the antibody response and neutralization potency. Here we employed glycoengineered Chinese hamster ovary (geCHO) cell lines that impart nearly homogeneous glycosylation as a means to test how specific glycan features influence antigenicity and immunogenicity for the secreted HCV E2 ectodomain (sE2). Specific geCHO antigens exhibited a modest but reproducible increase in affinity for some mAbs relative to CHO- and HEK293-produced sE2. Surprisingly, one geCHO sE2 antigen failed to bind the CD81 receptor, indicating the potential for significant glycan effects on biochemical properties. We immunized mice with the four antigens and found the total antibody response to be the same for all groups. However, sera from one geCHO group exhibited a 7-fold improvement in neutralization against the homologous HCV pseudovirus (HCVpp) and had the most mice whose sera exhibited neutralization activity against genotypes 1b, 2a, 2b, and 3. Further analysis identified beneficial and deleterious glycan features, and the glycan that correlated the most with decreased potency was relatively small. However, size was not the sole determinant of glycan-driven effects on the antibody response. In summary, glycan content impacts biochemical properties of antigens to varying degrees and such effects can influence immune response quality and uniformity.